The Balanced Scorecard as a Framework for Measuring International Joint Ventures Performance - Andreas Hoffjan; Martin Karlowitsch (Universitas Trisakti, 2013)
International joint ventures present a factor that becomes more and more important in the commercial activities of companies. However, the development of systems for performance measurement of joint ventures remains largely unsolved. In this article, the Balanced Scorecard is adjusted to the requirements of joint ventures. This concept is especially appealing for joint ventures, because mere financial performance measurement is absolutely inadequate, if non-financial goals are pursued by the joint venture-partners. It reduces the complexity of the decision-making process by its focus on critical success factors and their clustering into four perspectives. As the utilization of synergies and soft factors like mutual trust and harmony are crucial for the success of joint ventures, the authors suggest the addition of a cooperation perspective to incorporate these issues. The concrete application and the design of the different perspectives of a Balanced Scorecard are illustrated by the example of the Chinese-German joint venture Ameco.Key words : international joint venture; balanced scorecard; performance measurement, case study